Constructionalization, constructional competition and constructional death Investigating the demise of Old English POSS DEM constructions - Sommerer, Lotte (Nodes and Networks in Diachronic Construction Grammar, 2020)
This paper revisits POSS DEM constructions in Old English (OE) by analyzing 13 OE prose texts from the York-Toronto-Helsinki Parsed Corpus of Old English Prose (YCOE). It aims to explain the marginalization and ultimate demise of this constructional family by discussing how the emergence of a new node (“constructionalization”) but also the reorganization of node-external, vertical and horizontal links can lead to constructional competition and ultimately to the disappearance of (a) node(s) in the network. It will especially discuss frequency effects and cognitive factors like strong/weak entrenchment or analogical thinking as driving forces of network change, especially constructional loss. Additionally, this paper makes some suggestions on how constructions should be annotated and sketched in network
Keywords: Analogy; Constructional death; Co-occurrence of determinatives; Determination slot; Constructionalization; Nominal determination; Node loss